A Novel D‐A‐D Photosensitizer for Efficient NIR Imaging and Photodynamic Therapy. (7th May 2021) - Liu, Yuhan; Chen, MiaoMiao; Zhao, Yanliang; Lv, Shibo; Zheng, Daoyuan; Liu, Dapeng; Song, Fengling
Abstract: Photodynamic therapy (PDT) has attracted great interest in cancer theranostics owing to its minimal invasiveness and low side effect. In PDT, photosensitizers are indispensable components that generate cytotoxic reactive oxygen species (ROS). Tremendous efforts have been devoted to optimizing the photosensitizer with enhanced ROS efficiency. However, to improve the precision and controllability for PDT, developing NIR imaging‐guided photosensitizers are still urgent and challenging. Here, we have designed a novel photosensitizer 2Cz‐BTZ which integrated with intense NIR emission and photoinduced singlet oxygen 1 O2 generation capabilities. Moreover, after loading the photosensitizers 2Cz‐BTZ into biocompatible amphiphilic polymers F127, the formed 2Cz‐BTZ@F127 nanoparticles (NPs) exhibited good photoinduced therapy as well as long‐term in vivo imaging capabilities. Under these merits, the 2Cz‐BTZ@F127 NPs showed NIR imaging‐guided PDT, which paves a promising way for spatiotemporally precise tumor theranostics. Abstract : A novel D‐A‐D photosensitizer, 2Cz‐BTZ, was designed and synthesized. After encapsulation by amphiphilic polymers F127, the 2Cz‐BTZ@F127 NPs display strong intracellular 1 O2 generation capabilities as well as in vivo long‐term NIR imaging.